Implementasi Program Pengendalian Demam Berdarah Dengue di Kabupaten Donggala Sulawesi Tengah Tahun 2014 (Studi Kasus di Puskesmas Wani dan Puskesmas Labuan) - Aryani Pujiyanti; Anggi Septia Irawan; Wiwik Trapsilowati; Diana Andriyani Pratamawati; Ayun Sriatmi (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
The Donggala District Government has made efforts to control Dengue Hemorrhagic Fever (DHF), however based on the number of cases, and free larvae rates, DHF is still a public health threat in this area. The study aimed to evaluate the implementation of DHF control program in Donggala Regency. This was an evaluative descriptive qualitative research with a case study design. Research location in Donggala Regency, Central Sulawesi Province. Data was collected from September to October 2014 using a purposive sampling technique. Data validity carried out by source triangulation while data analysis was conducted by manually using content analysis. The informants were 10 persons from DHF control program staffs. Data was collected using in-depth interviews and document studies. The results showed that the budjet allocation on implementation of the DHF control program was lower than other infectious diseases. Cross-program collaboration has been carried out properly, however It is required more cross-sector collaboration for mosquito control program activities. From the output of program, the incidence rate (IR) of Donggala Regency was lower than IR of Central Sulawesi Province. Both Primary Health Care with low and high cases turn to have free larva index below 95% and those values tend to decrease in 2011-2012. Donggala District Health Office should increase the health promotion of DHF control through cross-sector collaboration and community to seek more awareness to the risks of transmission and improve dengue prevention.